EVALUATING INTEGRATIVE APPROACHES IN HEALTH ASSISTANCE AND NURSING: A CRITICAL REVIEW - Hamdan Ali Mohammed Al-Bahri, Hamad Mohammad Saad Al-Bahri, Mohammed Saleh Nasser Al Yami , Hamad Suayb Saleh Laslom, Nasser Mohamed AI Amer ‏‏, Mahdi Saleh Naseer Alyami, Nasser Saleh Nasser Al-Yami (Chelonian Research Foundation, 2023)
This article critically examines the integrative approaches within health assistance and nursing, aiming to uncover the potential benefits and challenges inherent in combining conventional medical practices with complementary and alternative therapies. With the healthcare landscape increasingly recognizing the value of holistic patient care, the integration of diverse therapeutic modalities has become a focal point for enhancing patient outcomes and satisfaction. This review delves into the historical evolution, core components, and current trends of integrative nursing, alongside a thorough investigation of its benefits, such as improved patient well-being and cost-effectiveness, and the obstacles it faces, including lack of standardization and issues with evidence base. Through an analytical lens, this article also explores practical case studies and future directions, advocating for a more robust evidence base, standardized protocols, and educational reforms to solidify the role of integrative approaches in mainstream healthcare. The critical insights provided herein aim to inform healthcare professionals, educators, and policymakers about the intricacies of implementing integrative practices, ultimately contributing to the advancement of patient-centered care. Keywords: Integrative Nursing, Health Assistance, Complementary Therapies, Patient-Centered Care, Holistic Health, Evidence-Based Practice, Healthcare Trends, Nursing Education, Policy Reform